Ensuring the well-being of the elderly: Revisiting the role and adequacy of social protection schemes in Malaysia and the Philippines - Abu Taher, Mohammad; Jamaluddin, Siti Zaharah; Yusoff, Jal Zabdi Mohd; Tahir, Zulazhar; Thambapillay, Sridevi (Universiti Utara Malaysia Press, 2018)
Globally, social protection schemes are considered as effective tools in ensuring the well-being of the poor, disempowered and otherwise marginalised people of society. It is applicable in cases of elderly people who are comparatively vulnerable due to their old age, and at times poverty or the lack of financial security. The proportion of elderly people in poverty is higher than that in the working age population, indicating the increasing likelihood of people falling into poverty as they leave or retire from the workforce. Therefore, one way of addressing poverty among the elderly is through social protection mechanisms. Malaysia and the Philippines are two Southeast Asian countries on their way to becoming ageing nations. As such, both these countries have already adopted numerous social protection schemes to ensure the well-being of the marginalised segments of society, including the elderly. Thus, based on existing literature, this paper is an attempt to revisit and re-examine the role and adequacy of existing social protection schemes available in Malaysia and the Philippines.